2008
DOI: 10.1021/jm800936s
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor Scaffolds for 2-Oxoglutarate-Dependent Histone Lysine Demethylases

Abstract: The dynamic methylation of histone lysyl residues plays an important role in biology by regulating transcription, maintaining genomic integrity, and by contributing to epigenetic effects. Here we describe a variety of inhibitor scaffolds that inhibit the human 2-oxoglutarate-dependent JMJD2 subfamily of histone demethylases. Combined with structural data, these chemical starting points will be useful to generate small-molecule probes to analyze the physiological roles of these enzymes in epigenetic signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
335
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 227 publications
(346 citation statements)
references
References 16 publications
11
335
0
Order By: Relevance
“…Recent reports showed that PrCa cell lines respond to MAOA inhibitors, possibly via inhibition of KDM's (Flamand et al, 2010). Furthermore, the JmjC-domain containing KDMs including PHF8 were found to be repressed by compounds targeting the Fe (II)/a-ketoglutarate dependent oxygenases (Cloos et al, 2006;Smith et al, 2007;Rose et al, 2008). Taken together, such compounds and epigenetic therapeutic concepts may offer intriguing starting points for the development of novel epigenetic therapies for PrCa.…”
Section: Discussionmentioning
confidence: 97%
“…Recent reports showed that PrCa cell lines respond to MAOA inhibitors, possibly via inhibition of KDM's (Flamand et al, 2010). Furthermore, the JmjC-domain containing KDMs including PHF8 were found to be repressed by compounds targeting the Fe (II)/a-ketoglutarate dependent oxygenases (Cloos et al, 2006;Smith et al, 2007;Rose et al, 2008). Taken together, such compounds and epigenetic therapeutic concepts may offer intriguing starting points for the development of novel epigenetic therapies for PrCa.…”
Section: Discussionmentioning
confidence: 97%
“…To evaluate whether compounds were inhibiting by binding to the active site (as opposed to, or in addition to, chelation of iron in solution), nondenaturing electrospray ionisation protein mass spectrometry (ESI MS) (Figure 2) was used to detect binding of compounds to the intact protein complex. [11] Although there are caveats on the use of mass spectrometry for screening binding strength, [17] the results of both assay methods correlated well (Table 1), with more potent compounds showing a stronger binding interaction with the protein complex by ESI MS.Previous work on inhibitors of the JMJD2 demethylases demonstrated that the parent compound 2,4-pyridinedicarboxylate is a 2OG-competitive inhibitor. This compound was shown by crystallographic analyses (PDB ID 2VD7) to bind the active-site metal via the pyridine nitrogen and the 2-carboxylate, while the 4-carboxylate is positioned to interact with the 2OG-binding residues Lys206 and Tyr132, effectively 'anchoring' the compound in the active site (see Figure 4).…”
mentioning
confidence: 85%
“…Although the situation with iron may be different to that for nickel (used for crystallography), these observations suggest that compounds such as 13a, 2,4-PDCA and 5-carboxy-8-hydroxyquinoline may inhibit JMJD2 Overall we have shown that modifications to the 4,4′-dicarboxy-2,2′-bipyridine template can result in substantial increases in potency against JMDJ2E (IC 50 of 6.6 μM for the lead compound 8a, while the most potent compound identified, 15c, had an IC 50 of 110 nM, which represents a 66-fold improvement in potency). [11] These increases in potency are, at least in part, likely mediated by both hydrophobic/π-π interactions and, in the case of some compounds (e.g. 13a), by electrostatic interactions.…”
mentioning
confidence: 99%
“…The amounts of NADH generated can be measured by absorbance at wavelength of 340 nm 235 or by fluorescence emission at 465 nm. [236][237][238] In addition to the measurement of formaldehyde, demethylated histone peptide products can be directly measured by MALDI-MS, 237,238 thus providing an optional approach for counterscreen or secondary assays of primary hits.…”
Section: B Biochemical Assays For Methyltransferase and Demethylase mentioning
confidence: 99%
“…80 A few inhibitors have been reported for JMJD demethylases that demethylate specific lysines in the H3 tail ( Figure 18). 237,[284][285][286] The analog of α-ketoglutarate, oxalyglycine, has been reported to be a weak inhibitor against JMJD2C 83 and the catalytic core of JMJD2A(c-JMJD2A). 284 Recently, Rose and coworkers demonstrated that HDAC inhibitors and pyridine carboxylic acids such as compound 6a and 7 ( Figure 18) act as micromolar inhibitors against JMJD2E (IC 50 : 1.4 μM for 6a and 6.6 μM for 7).…”
Section: E Inhibitors Of Histone Lysine Demethylasesmentioning
confidence: 99%